Serum vitamin D concentrations in young Turkish women with primary dysmenorrhea: A randomized controlled study - Osman Karacin; Ilknur Mutlu; Mesut Kose; Fatih Celik; Mine Kanat-Pektas; Mehmet Yilmazer (Elsevier, 2018)
Objective: This study aims to investigate the possible role of vitamin D deficiency in primary dysmenorrhea by assessing serum 25-hydroxyvitamin D3 levels in a cohort which includes young Turkish women with primary dysmenorrhea and healthy controls. Materials and methods: A total of 683 women who were aged between 18 and 25 years and who were consecutively admitted to the study center were eligible. After the exclusion of 55 women, 184 women with primary dysmenorrhea were randomly assigned into the dysmenorrhea group and 184 women without dysmenorrhea were randomly allocated into the control group. Results: The dysmenorrhea group had significantly less consumption of dairy products (p = 0.001), lower serum calcium (p = 0.001), lower serum vitamin D (p = 0.001) and higher serum parathyroid hormone (p = 0.001) than those of the control group. Hyperparathyroidism was significantly less frequent whereas vitamin D deficiency was significantly more frequent in the dysmenorrhea group (p = 0.001 for each). The dysmenorrhea patients with vitamin D deficiency had significantly higher visual analogue scale (VAS) scores (p = 0.001). Depression, irritability, mood swings, fatigue, headache and breast tenderness were significantly more frequent in the vitamin D deficiency group (p < 0.05 for all). The VAS scores of the dysmenorrhea patients correlated positively and significantly with serum parathyroid hormone levels (r = 0.666, p = 0.001) whereas these VAS scores correlated negatively and significantly with serum vitamin D levels (r = −0.713, p = 0.001). Discussion: The significant and positive correlation between vitamin D levels and VAS scores and the significant reduction in serum vitamin D levels of the dysmenorrhea patients designate the possible role of vitamin D deficiency in the primary dysmenorrhea.